Impact of quality of work life on performance level of adult and non formal education employees in Oyo and Lagos states (2010)
This study was carried-out to find out the impact of work life on performance level of adult and non-formal education employees in Oyo and Lagos slates. Nigeria. The descriptive survey of the ex-past facto type was adopted as the resign design. The population comprised all the employees of Adult and Non formal Education Agency in Oyo (167) and Lagos Stale (189) respectively. The sample size consisted of 50 respondents from each state and was randomly selected through the simple random sampling technique. A set of questionnaire lagged "Impact of Quality of Work Life and Performance Level of Employees Scale" (0.79) was used to obtain data for the four hypotheses postulated for the study. Data obtained were analysed through simple percentages and Pearson Product Moment Correlation Coefficient. Findings showed that there was a significant relationship between <0.05), organizational support and performance level (r=0.69 P <0.05). personal/family life and performance level (r=0.55 P <0.05), as well as personal health/wellbeing and performance level (r=0.55 P <0.05) of Adult and Non-Formal Education employees. Based on the findings, the study recommended that Adult and Non Formal Education Agencies have to intensify efforts, particularly in organizational policy and management style, towards improving the employees Quality of work life